Synthesis, characterization, and cytotoxic evaluation of Ag(I) NHC complexes derived from Theophylline - Pico Pérez, Alejandro Rodrigo (2024)
Abstract Natural products such as theophylline, caffeine, or theobromine have caught the attention to form organometallic complexes due to their pharmaceutical applications. In this sense, theophylline structure is an excellent scaffold for the preparation of NHC active complexes to favor metal-carbon bonds with almost any transition metal; have shown to be effective in obtaining organometallic compounds that show activities in different fields such as catalysis, pharmaceutical, and material science among others. In this work, a series of five Ag(I) theophylline-NHC complexes including fluorinated were synthesized and characterized using analytical techniques such as FT-IR, HPLC, NMR, mass spectroscopy, and single-crystal X-ray diffraction. Preliminary in vitro assays on the anticancer activity of five complexes obtained were performed in six human cancer cell lines; central nervous system glia (U251), prostate (PC-3), leukemia (K562), colon (HCT-15), breast (MCF-7), lung (SKLU) and compared with health monkey kidney cell line (COS-7). The results show that all five synthesized Ag(I) NHC complexes present high potency and specificity toward U-251 and K-562